2017
DOI: 10.15446/agron.colomb.v35n2.62772
|View full text |Cite
|
Sign up to set email alerts
|

Response of radish seedlings ( Raphanus sativus L.) to different concentrations of ammoniacal nitrogen in absence and presence of silicon

Abstract: Response of radish seedlings (Raphanus sativus L.) to different concentrations of ammoniacal nitrogen in absence and presence of siliconRespuesta de las plántulas del rábano (Raphanus sativus L.) a diferentes concentraciones de nitrógeno amoniacal en ausencia y presencia de silicio ABSTRACT RESUMENThere are unknown thresholds about the effects of ammonia toxicity in the cultivation of radish and its prejudice is higher in the root than in the aerial part, been the use of silicon an alternative to mitigate thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 23 publications
0
7
0
3
Order By: Relevance
“…Although the beneficial role of Si in the alleviation of different abiotic stresses is well documented, 5,13,18,19 little is currently known regarding the relevance of Si in the physiology of plants subjected to toxic levels of NH 4 + . We hypothesized that NH 4 + toxicity in radish seedlings might be mitigated by the incorporation of Si into the nutrient solution used in hydroponic cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the beneficial role of Si in the alleviation of different abiotic stresses is well documented, 5,13,18,19 little is currently known regarding the relevance of Si in the physiology of plants subjected to toxic levels of NH 4 + . We hypothesized that NH 4 + toxicity in radish seedlings might be mitigated by the incorporation of Si into the nutrient solution used in hydroponic cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…The high phytotoxicity observed, could be because of high ammonium content observed in the treatment (Figure 4), since radish is considered sensitive to high ammonium content. For instance, in the study conducted by Olivera Viciedo, et al [61] on the response of radish to difference ammonical nitrogen concentrations in absence and presence of silicon, observed highest sensitivity in treatments without silicon. In the cow manure treatment with E. fetida only, the highest germination observed agree with findings of Bernal, et al [62] who found increased GI value of radish from between 24 to 120 h of germination using cow manure vermicompost using E. fetida.…”
Section: 5mentioning
confidence: 98%
“…Nitrogen is the second most required nutrient by plants (Viciedo et al, 2017). It is an essential macro-element that participates in the synthesis of amino acids, nucleic acids, secondary metabolites, and components of the chlorophyll molecule.…”
Section: Introductionmentioning
confidence: 99%